Web based real time remote laboratory with labview access for analog and digital communication courses - (:unkn) unknown (My University, 2008)
With the rapid developments of internet and computer technologies, accessing and operating of real time applications is becoming reality. This study presents a real time web based laboratory on analog and digital communication experiments. The experiments are designed by using LabVIEW program for Marmara University Electronics and Communication Department. Also with the help of designed web site, the student can access the virtual laboratory and perform experiments without any limitation of time and location. The student can observe the signals by changing the parameters of the experiment and evaluate the results. During the session, the teacher can watch and communicate the student who performs his/ her experiment.
Keywords: Analog and digital modulation techniques; LabVIEW; Virtual laboratory